2013
DOI: 10.1007/s12011-013-9671-2
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of Breast Cancer Screening by PIXE Analysis of Hair

Abstract: To reveal the role of key elements present in the hair of breast cancer patients on cancer development, the levels of a number of elements in scalp hair samples of 82 people including healthy individuals, people suffering from benign breast disease, and breast cancer patients were measured by PIXE analysis. Pellets of hair samples were prepared and bombarded by 2.2 MeV proton beam of a 3-MV Van de Graaff accelerator. The number of incident ions hitting the sample was indirectly measured using the RBS spectrum … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 17 publications
0
11
0
Order By: Relevance
“…In this study, the average age of 43 women was 51.3 ± 11.5, which is less than screening populations (16) . Since in mammography there is radiation hazards to patients, and the sensitivity of …”
mentioning
confidence: 60%
See 2 more Smart Citations
“…In this study, the average age of 43 women was 51.3 ± 11.5, which is less than screening populations (16) . Since in mammography there is radiation hazards to patients, and the sensitivity of …”
mentioning
confidence: 60%
“…In addition, comparing the results of pathology as gold standard and mammography in detecting mammography is decreases with increase of age (16) , the goal of this study was to determine if differences between XRD curve of healthy women and breast cancer patients can lead to early detection of breast cancer or prediction of disease without radiation hazards or not.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A personal trace element profile for each patient that would include trace element measurements from tumor biopsies and serum may turn out helpful. For example, zinc/copper ratios and the estimation of trace element concentrations in hair samples may be of value 239 . Such trace element profiles and mutational analyses might also have prognostic value and guide treatment decisions for or against certain cancer therapies.…”
Section: Outlook and Possible Implications For Cancer Prevention Diamentioning
confidence: 99%
“…Other authors showed also that alterations in trace elements in plasma and cancer tissues were observed in patients with, for example, colorectal cancer [ 11 , 12 ], malignant breast tissues [ 13 ], malignant prostate [ 14 ], cancerous endometrial and ovarian tissues [ 14 ], and head and neck cancers [ 15 ]. Also, several studies have focused on the relationship between scalp hair trace element levels and cancer in patients from various geographical locations, that is, Turkey (Anatolia) [ 16 ], India (Malwa region, Punjab) [ 17 ], Pakistan (Rawalpindi district; Jamshoro) [ 6 , 18 21 ], Iran (Tehran) [ 22 ], Italy (Modena region) [ 23 ], and China (Guangdong Provence) [ 24 , 25 ] but not Poland. The role of trace elements in the development or inhibition of cancer remains to be fully elucidated.…”
Section: Introductionmentioning
confidence: 99%